Dampak Penggunaan Media Pembelajaran Berbasis Teknologi pada Mata Pelajaran Pendidikan Agama Islam di SMK Negeri 38 Jakarta - Siti Lutfiyyah; Heni Ani Nuraeni (Attractive : Innovative Education Journal, 2024)
The focus of this research aims to comprehend the application of teaching materials in the Islmaic Religious Education subject for the XI grade at SMK Negeri 38 Jakarta, to identify the learning media used in the Islamic Education in Islam subject for the XI grade at SMK Negeri 38 Jakarta, and to determine the impact of the use of teaching materials and techbology-based learning media for the XI SMK Negeri 38 Jakarta. This study used a descriptive qualitative method of analysis. Primary and secondary data sources are the ones that are employed. The respondents in this study are Islamic Religious Education teachers and XI grade student (culinary arts, hospitality, and fashion design). The result of this study indicate that the instructional resources for Islamic Republic of Education for XI grade pupil at SMK Negeri 38 Jakarta are quite good. Using educational materials to teach Islamic religion for XI grade students at SMK Negeri 38 Jakarta is also quite good and effective with the aid of projector technology and internet access. However, the researcher still found challenges, namely the limited use of projectors, as they are insufficient for the large number of classes. The impact of using technology-based teaching materials and learning media is very positive in supporting learning to achieve good, effective, efficient, and engaging learning objectives.